KRITIK AKADEMIK TERHADAP KHI ANTARA KODIFIKASI DAN DINAMIKA SOSIAL - Vern Subagya,; Erma Zahro Noor, (Journal of Innovation Research and Knowledge, 2026)
The Compilation of Islamic Law (KHI), established through Presidential Instruction No. 1 of 1991, is an effort to codify Islamic law in Indonesia, particularly in the areas of marriage, inheritance, and waqf. This article analyzes various academic critiques that have emerged against the KHI in the context of the dialectic between the need for legal codification and the social dynamics of Indonesian Muslim society. This study uses a normative-sociological approach by examining Islamic law literature, KHI documents, and various academic critiques that have developed. The results of the study show that the KHI faces several fundamental problems: its legal status is only a Presidential Instruction, its limitations in responding to contemporary social developments, and the tension between the classical fiqh approach and the need for legal reform. Critics also highlight aspects of gender justice, madhhab pluralism, and flexibility of interpretation. Nevertheless, the KHI continues to play a strategic role as a guide for religious courts and can serve as a basis for developing Islamic law that is more responsive to social dynamics